Performance Evaluation of a Multi-state System Covering Imperfect Fault Coverage - Ram, Mangey; Manglik, Monika (Communications in statistics. Simulation and computation, 2016)
Fault-tolerant networks are being used to provide more reliable network connections. Development of the fault-tolerant computing system requires accurate reliability modeling. Numerical formulations and complex models are commonly used for obtaining reliability measures. These measures are functions of component failure rates and fault-coverage. Coverage provides information about the fault and error detection, isolation, and system recovery capabilities. This research studied a system consisting three units in parallel with three types of failures namely, catastrophic, human, and unit failures incorporating the coverage factor and evaluated the various reliability measures of the considered multi-state system subject to imperfect fault coverage.